(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
Critical ‘self’ (i.e. dualist or egoist I) reflection seems insufficient in the context of Nepali university education, particularly in the process of transformative professional development. Therefore through this paper, I argue that a critical-appreciative approach contributes to my professional development. Assuming ‘Self’ (i.e. non-dualist or non-egoist I) as a better form of ‘self’, I conducted a self-study examining my conflict (between egoist I and non-egoist I) enhancing integral perspective. For it, I posed the research question: How could I nurture my integral perspective for my professional development in the higher educational context? I adapted dialogue as a research method to explore the conflict between ‘self’ and ‘Self’ with the support of my embodied knowledge, reflective journal, assignments and articles. In this paper, I discuss how my critical-appreciative approach enhanced my ‘self’ and at times remained a living contradiction. Then I discuss the four approaches as themes (adapting inclusive perspectives, creating open space, using participatory-based approach and developing tactful mentorship) that provided me with a cultural (i.e. satvic) perspective as professional development. These themes seem useful for understanding ‘self’ and the rest in an optimal way while being in higher education. आलोचनात्मक ’स्व’ (अर्थात् द्वैतवादी वा अहंकारी म) प्रतिबिम्ब नेपाली विश्वविद्यालय शिक्षाको सन्दर्भमा, विशेष गरी रूपान्तरणात्मकव्यावसायिक विकासको प्रक्रियामा अपर्याप्त देखिन्छ। यसैले यस पेपर मार्फत, म तर्क गर्छु कि एक आलोचनात्मक-प्रशंसनीय दृष्टिकोणले मेरोव्यावसायिक विकासमा योगदान गर्दछ। ’आत्म’ (अर्थात् गैर-द्वैतवादी म वा गैर-अहंकारी म) लाई ’आत्म’ को एक राम्रो रूपको रूपमा मान्दै, मैलेमेरो द्वन्द्व (अहंकारी म र गैर-अहंकारी म बीच) अभिन्न परिप्रेक्ष्यमा परिक्षण गर्दै आत्म-अध्ययन गरें। यसको लागि, मैले अनुसन्धान प्रश्न खडा गरें: उच्च शैक्षिक सन्दर्भमा मेरो व्यावसायिक विकासको लागि म कसरी मेरो अभिन्न दृष्टिकोणलाई पोषण गर्न सक्छु? मैले मेरो मूर्त ज्ञान, प्रतिबिम्बितजर्नल, असाइनमेन्ट र लेखहरूको समर्थनमा ’आत्म’ र ’आत्म’ बीचको द्वन्द्व अन्वेषण गर्न अनुसन्धान विधिको रूपमा संवादलाई रूपान्तरण गरें।यस पत्रमा, मैले कसरी मेरो आलोचनात्मक-प्रशंसनीय दृष्टिकोणले मेरो ’आत्म’ लाई बढायो र कहिलेकाहीं एक जीवित विरोधाभास बन्यो भनेरछलफल गर्छु। त्यसपछि मैले विषयवस्तुका रूपमा चार दृष्टिकोणहरू (समावेशी परिप्रेक्ष्यहरू अनुकूलन गर्ने, खुला ठाउँ सिर्जना गर्ने, सहभागितामा आधारित दृष्टिकोण प्रयोग गर्ने र कुशल मार्गदर्शनको विकास गर्ने) छलफल गर्छु जसले मलाई व्यावसायिक विकासको रूपमासांस्कृतिक (अर्थात् सात्विक) परिप्रेक्ष्य प्रदान गरेको छ। यी विषयवस्तुहरू उच्च शिक्षामा रहँदा ’आत्म’ र बाँकीलाई बृहत तरिकाले बुझ्नको लागिउपयोगी देखिन्छन्।